2023
DOI: 10.1002/jmri.28642
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multiparameter Quantitative Magnetic Resonance Imaging in the Evaluation of Graves' Ophthalmopathy

Abstract: BackgroundAssessment of the activity of Graves' ophthalmopathy (GO) is difficult. Existing methods need improvement.PurposeInvestigate the application of multiparametric magnetic resonance imaging (MRI) in GO.Study TypeRetrospective.PopulationA total of 235 GO patients (age: 38.8 ± 13.4 years; 90 male; 96 active patients).Field Strength/SequenceShort‐tau inversion recovery (STIR) fast spin echo, multiecho spin echo T2 mapping and 3D T1‐weighted fast field echo sequences at 3.0 T.AssessmentTwo physicians assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(96 reference statements)
0
0
0
Order By: Relevance
“…The involvement of EOMs is a known disease process in patients with TAO [ 16 , 17 ]. In this study, we found that the SIR min/mean/max values of EOMs were significantly greater in active TAOs than those in inactive TAOs, consistent with previous studies [ 18 , 19 ]. In addition, using the Dixon MRI technique, our study indicated that active TAOs had higher water-related metrics (EOM-WF mean and EOM-WF min ) and lower fat-related parameters (EOM-FF max and EOM-FF mean ) than did inactive TAOs.…”
Section: Discussionsupporting
confidence: 93%
“…The involvement of EOMs is a known disease process in patients with TAO [ 16 , 17 ]. In this study, we found that the SIR min/mean/max values of EOMs were significantly greater in active TAOs than those in inactive TAOs, consistent with previous studies [ 18 , 19 ]. In addition, using the Dixon MRI technique, our study indicated that active TAOs had higher water-related metrics (EOM-WF mean and EOM-WF min ) and lower fat-related parameters (EOM-FF max and EOM-FF mean ) than did inactive TAOs.…”
Section: Discussionsupporting
confidence: 93%
“…The signal intensity in ipsilateral brain white matter regions of interest was measured three times on coronal water-phase Dixon-T2WI images showing the maximum white matter area of each brain, and an average was taken ( Figure 1C ). The ratio of the maximum signal intensity of LPS to the mean signal intensity of brain white matter (LPS_SIR) was calculated ( 27 , 28 ).…”
Section: Methodsmentioning
confidence: 99%